Optimalisasi Penggunaan Google Classrom Dalam Upaya Meningkatkan Pengetahuan Media Pembelajaran pada Guru MAS Tarbiyyah Islamiyah Hamparan Perak - Danny Abrianto; Tumiran Tumiran; Hadi Saputra Panggabean (Maslahah: Jurnal Pengabdian Masyarakat, 2023)
The use of learning media through Google Classroom in Indonesia is still very little used. This learning media has been widely used during the Covid-19 period for the last two years as a form of effort so that teachers who have not been familiar with advances in educational technology can support their ability to process information and technology-based learning media. The method used in this research is to conduct training and practice for teachers at MAS Tarbiyah Islamiyah Hamparan Perak by providing descriptions and the impact of optimizing the use of learning media through Google Classroom which can be linked to various references from several sources of learning media and displaying slides by collecting teachers at MAS Tarbiyah Islamiyah Hamparan Perak so that future teachers can be motivated and innovate in optimizing the use of learning media and be more creative in pursuing information technology and computers in the digitalization era.